D10.1 Report on the dissemination activities and Conference organisation - Loulli, Eleni; Prodromou, Maria; Papoutsa, Christiana; Hadjimitsis, Diofantos G.; Themistocleous, Kyriacos; Neocleous, Kyriacos; Schreier, Gunter; Schwarz, Egbert; Krauss, Thomas; Kontoes, Haris; Kaskara, Mariza; Ansmann, Albert; et al. (My University, 2021)
This deliverable provides an extensive analysis of the dissemination activities and workshops organisation of the EXCELSIOR H2020 Teaming Project. The analysis starts with the report on our participation in conferences (11) and how the project was promoted through it. Then, we explain about the participation of our team members in talks (17), workshops (7) and seminars (12) as invited speakers. The deliverable continues with a thorough presentation of the lectures by invited speakers (8), the webinar (1) and the workshops (2) organized by our team. Additionally, we document about our participation in other events (i.e., European Researcher’s Night 2021 and SpaceUPCyprus 2021 Live). The last chapter provides the publications, journal papers, conference papers, and book sections for the reporting time period. The deliverable concludes by providing information on the outcome of the reported activities and how they have contributed to the progress of the EXCELSIOR H2020 Teaming Project. It is concluded that there is a strong need to establish links in the EMMENA region and connect with them. This has not been achieved yet, but a strategy was prepared to raise awareness about the EXCELSIOR Project in the EMMENA region and establish partnerships, starting with targeted stakeholders’ workshop in autumn 2021, where selected stakeholders from the region will be invited to be informed them about the project and provide them the space to discuss their needs and identify common scientific interests and ways of collaboration.
Keywords: ERATOSTHENES; Remote Sensing; EXCELSIOR; HORIZON H2020; EMMENA